Holistic approaches to reducing Salmonella contamination in poultry industry - Abdul Rahiman, Ummu Afiqah; Nordin, Noordiana; Abdul Mutalib, Noor Azira; Sanny, Maimunah (Universiti Putra Malaysia Press, 2021)
Salmonella are widely found in the poultry industry, which subsequently may pose a risk to animal and human health. The aim of this review is to highlight strategies for the prevention and control of Salmonella at each stage in the poultry production chain by monitoring risks from the farm to the retailer. Among the primary approaches for control of Salmonella at the farm level includes the administration of synthetic and natural compounds to live chickens (vaccination and antibiotic), litter management as well as fortification of feed and acidification of drinking water. In the poultry processing plant, multiple hurdle technology and different chilling conditions to reduce Salmonella were discussed. In the retail level, an effective monitoring program to control Salmonella contamination by good manufacturing practices and hazard analysis and critical control points has been reviewed. Overall, we conclude that these approaches play a role in reducing the dissemination of Salmonella in the poultry industry. However, there is no published data related to logistic scheduling of poultry processing.